O idoso brasileiro na comunicação pública: cidadania e representações sociais num sistemade interaçãomidiático - Stacheski, Denise Regina (2013)
The thesis, "The Brazilian Elderly in Public Communication" aims to study general social representations of the elderly through a media interaction system, linked to the dialogue processes of public communication in Brazil, through three components: promoter’s policies, media producers and individual actors. In order methodological content analysis of Bardin (2011) was the method guiding the study, through qualitative and quantitative techniques. Without pretension to outline practical actions for public communication, the thesis makes a diagnosis in the circulation of social representations of aging policies between promoters, producers, media and individual actors. Throughout the thesis were presented and analyzed empirical objects brazilians (official website of the Ministry of Health - Health Portal, media coverage of the National Campaign Against Violence Awareness of Elderly and elderly publications on Facebook). In conclusion, we found that the victimization of the elderly is present in the circulation of social representations of aging, mainly by means of media producers. However, we also have found voices of resistance from individual actors in digital social networks, compared to negative representations of aging. Promoters of political and media producers use with intensity, the term "elderly" and "aging" homogeneously - strengthening the stigma of old age with social frailty or physical degeneration. The official website of the Ministry of Health focuses its communicative units for the transfer of information about disease prevention - there were no strategies for activation of civic participation among the elderly. It was found also that the use of social networks for enabling the participation of older people in public deliberation can be a way to build a direct dialogue with brazilian elderly, respecting their diversity and heterogeneity.